Imagining coastal change: reflections on making a film - Daniels, Stephen; Veale, Lucy (Sage, 2013)
Geography has a long, if episodic, relationship with film and film-making. In this essay we reflect on the process of making the short film Imagining Change: Coastal Conversations during the first three months of 2012. We discuss some issues arising from the making of the film as a medium and method for showing, and showcasing different forms of arts and humanities practice – narrating, performing, picturing – in relation to environmental change.